Real time device control over voice recognition inoffline - Rukkumani, C; Krishna Mohanta.S, Dr; S, Govindaraj (International Journal of Engineering and Technology, 2018)
The consistent increase in the number and ownership population of mobile devices introduces a variety of limitations. A set of this limitations revolve around interactivity. The overly dependent haptic mechanism of interaction has caused device falls, slower time to interaction, health concerns, and limited support for the disabled among other problems. There is need to formulate innovative techniques that facilitate our interaction with these devices for users. In order to achieve this, a Real-time Voice Recognition Algorithm is formulated that lets users of mobile devices acquire freedom to move about and reduce the need for constantly glancing at their screen. This is achieved by allowing users to verbally command their devices to carry out ordinary tasks. An added unique feature is that it also offers offline access as any commands given by a user are processed and executed locally on the device.